Existential security of women in post-2003 Society - Abdul Kareem, Hiba Abdul Mohsin (Al-Adab Journal, 2021)
My work in this research was to get acquainted with the most important facts about the existential security of Iraqi women after the events that occurred in Iraqi society in 2003. As many inhumane issues surfaced that raided the security of women and forced them to cope with those crises. The state of security and stability, the importance of self-respect and the feeling of existential fulfillment of human life, is a fundamental test for the enjoyment of man, especially women, of the most basic human rights that God Almighty has granted to human beings. The danger that has become a death toll at any place and time, the spread of terrorist ideology, manifestations of violence and discrimination based on gender, institutional defects and the spread of poverty in society, have made women cheap and lacks their existential security on the face of the earth. Herein lies the problem. The importance of research stems from the importance of what women represent in society, and what many organizations and conferences concerned with human rights have called for regarding the importance of the security situation as a basic source of life, and the sense of reassurance leads the individual to initiate and contribute to achieving development goals. As for its objectives, it was summarized in highlighting the nature of the existential security of Iraqi women, and standing on the most prominent images and violations of the existential security of women after the events of 2003. In order to reach the safety compound for the security of Iraqi women, we tried to find out what the state of danger produces through the destructive images that it reviewed of violations of the existential security of women in Iraq. And its effects are still rooted in society. Then we tried to present some conclusions drawn from the research. We concluded by presenting some recommendations and proposals that would address the insecurities that women face in society. We hope to contribute to changing the stereotype rooted in the mind and spirit of society, which views women with a narrow view and considers them a second-class individual, trying to bring them to the right of the existential security that they deserve.